Kontribusi Yayasan Pendidikan Islam Tellungpoccoe (YAPIT) Terhadap Perkembangan Pendidikan Islam di Kecamatan Amali Kabupaten Bone - Mustafa, Mustafa (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research examines the contributions of Islamic Education Foundation Tellungpoccoe (YAPIT) against the Islamic Education in district Perkebangan Amali Bone Regency. To get information about it, then the researcher is using educational approaches, psychological, sociological, and historical. In the data collection used method of observation, interview and documentation. The results showed that the contribution of the Islamic Education Foundation Tellungpoccoe (YAPIT) towards the development of Islamic education in district Amali Bone Regency is very good. It is marked by the start of the establishment of Islamic Education Foundation Tellungpoccoe (YAPIT) Taretta to date has given a good Role on the development of Islamic education in district Amali Bone Regency. Where since its foundation up to now this has set up educational institutions such as: the year of 1986 established the kindergarten YAPIT Taretta still active until now, year 1987 establishing kindergartens Bali Sumange active till now in 1988 founded the Madrasa Aliyah private (MAS) YAPIT Taretta active till now, and in the same year set up boarding schools Taretta YAPIT. In 1990 set up Mts (MTs) YAPIT Taretta is also active to this day. And in 2006 established the MDU (Madrasah Diniyah Ula) YAPIT Taretta.